2007
DOI: 10.1021/ja0745613
|View full text |Cite
|
Sign up to set email alerts
|

Control of Calcium Oxalate Crystal Growth by Face-Specific Adsorption of an Osteopontin Phosphopeptide

Abstract: Mineral-associated proteins have been proposed to regulate many aspects of biomineralization, including the location, type, orientation, shape, and texture of crystals. To understand how proteins achieve this exquisite level of control, we are studying the interaction between the phosphoprotein osteopontin (OPN) and the biomineral calcium oxalate monohydrate (COM). In the present study, we have synthesized peptides corresponding to amino acids 220-235 of rat bone OPN (pSHEpSTEQSDAIDpSAEK), one of several highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
172
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(190 citation statements)
references
References 58 publications
16
172
0
2
Order By: Relevance
“…The formation of these compositional zoning patterns in COD crystals was confirmed by laser scanning confocal microscopy ( Fig. 4c), which enables "optical sectioning" to exclude out-of-focus flare and, thus, allows direct imaging of crystal interiors (20). These two-dimensional zoning patterns vary in appearance with the "depth" of the optical focus and allowing confirmation of the sectoral zoning through different focal planes (Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The formation of these compositional zoning patterns in COD crystals was confirmed by laser scanning confocal microscopy ( Fig. 4c), which enables "optical sectioning" to exclude out-of-focus flare and, thus, allows direct imaging of crystal interiors (20). These two-dimensional zoning patterns vary in appearance with the "depth" of the optical focus and allowing confirmation of the sectoral zoning through different focal planes (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Fluorescent molecules and fluorescently-tagged proteins have been previously and effectively used to study protein-mineral interactions (in COM studies (19,20,(77)(78)(79)). Extending this approach to COD and using a poly-Asp 86 -93 peptide not previously examined by others, we have visualized by light and confocal microscopy the incorporation behavior of this peptide into the crystal structure of COD and revealed distinctive and informative three-dimensional sectoral (compositional) zoning patterns (77)(78)(79)(80) that provide significant new insight into protein occlusion into biominerals.…”
Section: Discussionmentioning
confidence: 99%
“…Its ubiquitous expression pattern and variations in phosphorylation, glycosylation and sulphation suggest that OPN fulfills many different functions (George & Veis, 2008). Moreover, OPN controls the formation of calcium phosphate (Goldberg & Hunter, 1995), calcium carbonate (Chien et al, 2008), and calcium oxalate (Grohe et al, 2007) crystals. NMR, CD and FTIR studies demonstrated that OPN is an IDP in solution (Tab.1) (Fisher et al, 2001;Gorski et al, 1995).…”
Section: Opnmentioning
confidence: 99%
“…Interactions between proteins and crystals, including OPN peptides (Grohe et al 2007), are central to many processes in biomineralisation. The inorganic core of dehydrated CPN samples has however been found to be amorphous, based on experimental results from a range of techniques including electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy (FTIR) and X-ray absorption spectroscopy (Cross et al 2005;Holt et al 1982Holt et al , 1996Holt et al and 2009Hunter et al 1996;Holt and Hukins 1991).…”
Section: Introductionmentioning
confidence: 99%